“Inorganic Chemistry”, de G. L. Miessler, P.J. Fisher, D. Tarr - Ortega San Martín, Luis (2014)
Short review of the most important and interesting sections of the 5th edition of the inorganic chemistry textbook written by G. L. Miessler, P.J. Fisher and  D. Tarr. Published by Pearson, New Jersey, 2014. 682 pages. ISBN: 978-0321811059